Empowerment of Fisherwomen through Self-Help Groups: A Multidimensional Impact Assessment in Thoothukudi, Tamil Nadu, India - V. Rajkumar,; S. Boopathi,; Jatav, Surendra Singh (Indian Journal of Extension Education, 2024)
The unpredictable nature of marine fisheries leads to unstable earnings, rendering fisherwomen vulnerable to financial insecurity and marginalization. The study evaluated the impact of self-help group (SHG) participation on their multidimensional empowerment across a sample of 240 SHG members of four coastal villages namely Threspuram, Vellapatti, Tharuvikulam, and Periyathalai in Thoothukudi district, Tamil Nadu, India during 2023. The SHG membership has led to significant improvements in the economic well-being of fisherwomen. After joining SHGs, participants experienced substantial increases in their monthly income (from Rs. 2,075 to Rs. 6,875), expenditure (from Rs. 1,981 to Rs. 4,671), and savings (from Rs. 1,166 to Rs. 2,633). The SHG membership has substantially enhanced participants' understanding of social issues, educational opportunities, financial management, and engagement with government programs. The suggestions include scaling up SHG initiatives, improving access to credit and markets, fostering skill development and entrepreneurship to promote the empowerment of fisher women and enhance the sustainability of coastal communities.